Bioatividade de Punica granatum no reparo de lesões infectadas - FONTOURA, Guilherme Martins Gomes (2021)
Introduction: The goals of wound care are to prevent infections, reduce swelling and inflammation, accelerate healing, and minimize scarring. However, the healing process can be aggravated by factors such as poor circulation at the wound site and microbial infection. The increase in antibiotic resistant pathogens makes the healing treatment of infected wounds less effective and leads to the search for new therapeutic agents effective against these bacteria. Therefore, the exploration of new natural healing compounds is important. Among them, the plant species Punica granatum popularly known as pomegranate has been widely used as a medicine for the treatment of various diseases. Objectives: To verify the antibacterial and healing potential of the crude extract of P. granatum on an infected wound healing model. Material and Methods: To evaluate the antibacterial activity of P. granatum extract (EHPg) the in vitro agar diffusion method was used. The antioxidant activity of EHPg was also verified by the DPPH and ABTS tests. For the healing model, the animals were randomly divided into three groups (n=12), including negative control (CTRL); Fibrinase® (DFC, positive control); and a formulation based on EHPg as a research group. Wound diameter and healing percentage were investigated with the help of ImageJ software. Macroscopic analysis of the wounds was performed every other day. Randomly, animals from each group were euthanized on days 3, 7 and 10 and then the wounded skin was removed for pathological studies. Finally, the count of colony forming units (CFU) present in the wounds was analyzed to verify the antibacterial activity of EHPg in vivo. Results: EHPg inhibited the growth and proliferation of all strains tested. It was observed that EHPg inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA) at all test concentrations, with statistical differences for the highest concentrations, ranging from 18.67-21.33 mg/mL (p<0 .05). The free radical scavenging potential of EHPg was tested by the DPPH method, showing an IC50 = 4.01 μg/ml. While in the ABTS method, the EHPg presented with IC50 = 40.62 μg/ml. Topical wound treatment of mice with infected wounds induced complete wound retraction on day 10 in all groups. Treatment with EHPg did not result in an acceleration of the healing process. Regarding in vivo antibacterial activity, on day 3 microbial growth was observed in all groups. The CFU plates from the CTRL group showed high growth compared to the DFC and EHPg groups. On day 7, the growth was classified varying from little to medium for the CTRL group, while in the DFC and EHPg groups no growth and little growth were observed, respectively. On day 10, growth of CFU was again observed in all groups, with medium growth in the CTRL and EHPg groups, and varying from no growth to high growth in the CFD-treated group. Conclusions: In this study, EHPg showed inhibition of bacterial growth of several strains in vitro, with great inhibitory activity on MRSA. Despite not speeding up the healing process, EHPg was able to reduce the proliferation of MRSA in infected lesions. EHPg contributed to improve the formation of the new structure of the injured tissue, facilitating the healing process by controlling inflammation, fibroblast proliferation and abundant collagen deposition.